Antibodies against the majority subunit of type IV pili disperse nontypeable Haemophilus influenzae biofilms in a LuxS‐dependent manner and confer therapeutic resolution of experimental otitis media. Issue 2 (15th February 2015) - Novotny, Laura A.; Jurcisek, Joseph A.; Ward, Michael O.; Jordan, Zachary B.; Goodman, Steven D.; Bakaletz, Lauren O.
Summary Despite resulting in a similar overall outcome, unlike antibodies directed against the DNABII protein, integration host factor (IHF), which induce catastrophic structural collapse of biofilms formed by nontypeable Haemophilus influenzae (NTHI), those directed against a recombinant soluble form of PilA [the majority subunit of Type IV pili (Tfp) produced by NTHI], mediated gradual 'top‐down' dispersal of NTHI from biofilms. This dispersal occurred via a mechanism that was dependent upon expression of both PilA (and by inference, Tfp) and production of AI‐2 quorum signaling molecules by LuxS. The addition of rsPilA to a biofilm‐targeted therapeutic vaccine formulation comprised of IHF plus the powerful adjuvant dmLT and delivered via a noninvasive transcutaneous immunization route induced an immune response that targeted two important determinants essential for biofilm formation by NTHI. This resulted in significantly earlier eradication of NTHI from both planktonic and adherent populations in the middle ear, disruption of mucosal biofilms already resident within middle ears prior to immunization and rapid resolution of signs of disease in an animal model of experimental otitis media. These data support continued development of this novel combinatorial immunization approach for resolution and/or prevention of multiple diseases of the respiratory tract caused by NTHI.